Difference Of Fetal Weight Between Conventional vs Electric Smoke Exposure in Mice (Mus Musculus) - Kusumastuti, Nurry Ayuningtyas; Haeriyah, Siti; Susilowati, Yuni (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: The increase in tobacco excise rates (CHT) or cigarette excise in early 2020 is a reason for smokers to switch to using e-cigarettes. WHO reports that about 64.9% of adult men in Indonesia are smokers, while in women it is 2.1%. This shows that Indonesia is ranked first in the world. Exposure to e-cigarettes and conventional cigarettes will affect pregnancy and the fetus it contains. However, in reality, most people have the perception that e-cigarettes are safer than conventional cigarettes because their nicotine content is much lower than conventional cigarettes. The purpose of this study was to analyze differences in exposure to e-cigarettes and conventional cigarettes on fetal weight in mice (mus musculus).Subjects and Method: This study used a true experimental design which was divided into two groups, namely 16 female mice as a group given exposure to e-cigarettes and 16 female mice as a group being exposed to conventional cigarettes. The dependent variable is the weight of the fetus. The independent variables were exposure to e-cigarettes and conventional cigarettes. The instrument in this study used a digital gold scale with an accuracy of 0.01 gram. Data were analyzed using the Mann Whitney test.Results: On average, exposure to e-cigarettes had a greater fetal weight (Mean= 1.61; SD= 0.64) than exposure to conventional cigarettes (Mean= 1.48; SD= 1.19), and this result was statistically significant (p < 0.001).Conclusion: There are differences in exposure to e-cigarettes and conventional cigarettes on fetal weight in mice (Mus musculus).